On the Process of Civilisation in Japan Sociogenetic and Psychogenetic Investigations - Lau, Wai. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
"On the Process of Civilisation in Japan is one of the most important books that have recently been written from an Eliasian perspective. ... [T]he author successfully demonstrates that Norbert Elias's figurational theory can be applied to Asian countries like Japan, encouraging us to build new sociological models on that basis." -Akira Ohira, Professor Emeritus, Waseda University, Japan "... His work is grounded in a thorough understanding of the comparative and historical theory of civilization and a deep knowledge of the evolution of Japanese society - a unique combination that makes this study an indispensable source for students of Japan and for anyone interested in the process of civilization across continents." -Abram de Swaan, Professor Emeritus, University of Amsterdam, Netherlands "This important book uses Norbert Elias's theory of civilising processes to interpret the broad sweep of Japanese history ... A most ingenious feature, in the absence of Japanese counterparts to European 'manners books', is the detailed account of the long-term development of the celebrated Japanese 'tea ceremony'." -Stephen Mennell, Professor Emeritus, University College Dublin, Ireland This book charts the process of civilisation in Japan. Using the theory of civilising processes developed by Norbert Elias, the author examines the complex underlying structural and psychological processes from the seventh century to the twentieth century. Furthermore, by drawing on rich historical data, the author illustrates how these complex processes led the Japanese to see themselves as 'more civilised' than their forebears and neighbouring countries. Although the theory serves as an important reference point, the author draws on other works to address different complex questions surrounding Japanese development. Therefore, this book presents three key themes: first, it gives an alternative understanding of the complex developments of Japanese society; second, it intercedes into an ongoing debate about the applicability of Elias's theory in a non-Western context; and third, it expands Elias's theory. Wai Lau is Researcher in Sociology at the University of Manchester, UK.
Chapter 1: Introduction -- Part I: The Theory of Civilising Processes -- Chapter 2: The Concept of 'Civilisation' and 'Culture' -- Chapter 3: The Psychogenetic Development of the Civilising Process -- Chapter 4: The Sociogenetic Development of the Civilising Process -- Chapter 5: Criticisms and Counter Criticisms of the Civilising Process -- Part II: On the Concepts of 'Civilisation' and 'Culture' in Japan -- Chapter 6: Japanese Civilisation -- Chapter 7: The Dual-Lenses of Japanese Civilisation -- Chapter 8: The Japanese Antithesis between 'Civilisation' and 'Culture' -- Part III: Towards the Change of Behaviours, Emotions, and Habitus in Japan -- Chapter 9: The Medieval Form of the Japanese Tea Ceremony -- Chapter 10: The Early Modern Form of the Japanese Tea Ceremony -- Chapter 11: The Modern Form of the Japanese Tea Ceremony -- Part IV: Scenes from the Life at the Court Society in Japan -- Chapter 12: Scenes of Life from the Imperial Court Society in Kyoto -- Chapter 13: Scenes of Life from the Warrior Court Society in Edo -- Chapter 14: Scenes of Life from the Chrysanthemum Court Society in Tokyo -- Part V: Towards the Process of Pre-Modern and Modern State Formation in Japan -- Chapter 15: The Imperial State Formation Processes of Japan -- Chapter 16: The Warrior State Formation Processes of Japan -- Chapter 17: The Modern State Formation Processes of Japan -- Chapter 18: Conclusion.
Keywords: Sociology; Culture; Japan-History.; Ethnology-Asia.; Sociological Theory; Sociology of Culture; History of Japan; Asian Culture